Peningkatan Efisiensi Pembaruan Aplikasi Android Tap On Bus Menggunakan Sistem OTA Update Berbasis REST API - Rohmat Julianto; Mutaqin Akbar (Forum Kerjasama Pendidikan Tinggi (FKPT), 2026)
Managing application updates for more than 400 Android validator devices of the Tap On Bus system, deployed across various public transportation routes in Indonesia, presents significant challenges in efficiency and scalability. The existing manual update process, relying on physical storage media (flash drives) and direct technician intervention at each device location, has proven inefficient, poses risks to data integrity, and causes version inconsistencies across devices. Using commercial Mobile Device Management (MDM) platforms as an alternative also introduces vendor dependency and high recurring license costs. This research aims to develop and implement an independent (in-house) Over-The-Air (OTA) Update system based on REST API to automate the centralized and remote distribution and installation of Android application updates. The system was developed using the Research and Development (R&D) method with the Waterfall model, implemented using Go (Golang) for the REST API backend with a MySQL database running on the XAMPP web server, Kotlin with the PackageInstaller API for the Android client on Telpo T10 devices, and the Vuetify framework for the monitoring dashboard. Functional testing using the Black Box Testing method across 19 test scenarios covering device registration, startup-triggered update checking, version validation, APK package download, download-failure and installation-failure handling with recovery, and automatic installation yielded a 100% success rate. Comparative analysis demonstrated that the OTA system successfully reduced the average update time per device from 16 minutes (manual) to approximately 1.2 minutes (automatic), equivalent to a 92.5% efficiency improvement, while eliminating technician travel costs. The system also demonstrated the ability to maintain transaction data integrity during updates and centrally log all update activities in the database, confirming its readiness for deployment in large-scale public transportation environments.